PENGARUH INVENTARISASI DAN PENILAIAN ASET TETAP/BARANG MILIK DAERAH TERHADAP PERSEPSI PENYAJIAN NILAI WAJAR NERACA DI PEMERINTAH KOTA BANJARBARU - , RATIH RISTIASIRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to analyze the effect of inventory in the form of logging, coding, grouping, recording and fixed assets valuation against to real fair value perception of balance sheet Banjarbaru Local Government. The analysis tools used are multiple regression with spss 21.0 software. The estimation of multiple regressionaims to seeing the influence of independent variables against to dependent variables in partial and collective. The analysis results to prove alternative hypothesis with the equations model are y = 2,236 + 0,153X1- 0,278X2- 0,036X3 + 0,315X4 + 0,141X5 which is concluded that the most influence variables perception of real fair value perception of balance sheet Banjarbaru Local Government is valuation variable (X5) with a level of significance is 0,000. The second one is recordingvariable (X4) with a level significance is 0,011. The other variables that affect the dependent variable is logging variables (X1) with a level of significance is 0,036 and coding variable (X2) which had a level of significance is 0,015. All of the The steps should be enhanced in asset management atprocess of inventorywork and valuation to improve fair value ofbalance sheet BanjarbaruLocal Government by increasing the quality of the database through a Regional Asset Management System (Sistem Manajemen Aset Daerah (SIMADA)) that have been run, to reactivate the proceduresof operationalsystem (Sistem Operasional Prosedur (SOP)) in the management of fixed assets in order to straight, efficient, effective and accountable, census ofphysic checksand document checks periodically to a unitof work is assisted by a prepared work program, memo paper was provided to note if any case of grant outside of office hours which assisted with training to improve of the importance understandingabout local government property management well and asset valuation withone of combination approachfrom comparason of market data, calculation of costs and income capitalization according to the domestic decision No. 12 on 2013 about Valuation of Property Local Government.